Answer:
your answer is the attached image below. Let me know if its right. I am 99.99% sure XD
Explanation:
How u get the answer is by Rewriting the equation as
-(x+3)(2x-1)(x+b)=12
Then you apply the distributive property. * = multiplication
(-x-1*3)(2x-1)(x+b)=12
Then multiply -1 by 3
(-x-3)(2x-1)(x+b)=12
Divide each term in the expression above by (-x-3)(2x-1) and simplify
(-x-3)(2x-1)(x+b) / (-x-3)(2x-1) =
12 / (-x-3)(2x-1)
Then simplify the left side, cancel the common factor of -x-3, and rewrite.
(2x-1)(x+b) / 2x-1 =
12 / (-x-3)(2x-1)
Now cancel the common factor of 2x-1, and divide x+b by 1
x+b=12 / (-x-3)(2x-1)
Simplify the right side, and factor -1 out of -x
x+b= 12 / (-(x)-3))(2x-1)
Rewrite -3 as 1(3)
x+b= 12 / (-(x)-1(3))(2x-1)
Factor -1 out of -(x)-1(3)
x+b= 12 / -(x+3)(2x-1)
Rewrite negatives (Rewrite -(x+3) as -1(x+3)
x+b= 12 / (x+3)(2x-1)
Move the negative in front of the fraction.
x+b= -12 / (x+3)(2x-1)
Subtract x from both sides of the equation.
b= -12 / (x+3)(2x-1)
There you go thats your answer! Hope it helped :)